Design of an Optimized Wilms' Tumor 1 (WT1) mRNA Construct for Enhanced WT1 Expression and Improved Immunogenicity In Vitro and In Vivo - Daphné Benteyn; Sébastien Anguille; Sandra Van Lint; Carlo Heirman; An MT Van Nuffel; Jurgen Corthals; Sebastian Ochsenreither; Wim Waelput; Katrien Van Beneden; Karine Breckpot; Viggo Van Tendeloo; Kris Thielemans; et al. (Elsevier, 2013)
Tumor antigen-encoding mRNA for dendritic cell (DC)-based vaccination has gained increasing popularity in recent years. Within this context, two main strategies have entered the clinical trial stage: the use of mRNA for ex vivo antigen loading of DCs and the direct application of mRNA as a source of antigen for DCs in vivo. DCs transfected with mRNA-encoding Wilms' tumor 1 (WT1) protein have shown promising clinical results. Using a stepwise approach, we re-engineered a WT1 cDNA-carrying transcription vector to improve the translational characteristics and immunogenicity of the transcribed mRNA. Different modifications were performed: (i) the WT1 sequence was flanked by the lysosomal targeting sequence of dendritic cell lysosomal-associated membrane protein to enhance cytoplasmic expression; (ii) the nuclear localization sequence (NLS) of WT1 was deleted to promote shuttling from the nucleus to the cytoplasm; (iii) the WT1 DNA sequence was optimized in silico to improve translational efficiency; and (iv) this WT1 sequence was cloned into an optimized RNA transcription vector. DCs electroporated with this optimized mRNA showed an improved ability to stimulate WT1-specific T-cell immunity. Furthermore, in a murine model, we were able to show the safety, immunogenicity, and therapeutic activity of this optimized mRNA. This work is relevant for the future development of improved mRNA-based vaccine strategies K.